2014
DOI: 10.14434/v14i4.3895
|View full text |Cite
|
Sign up to set email alerts
|

“Who am I to bring diversity into the classroom?” Learning communities wrestle with creating inclusive college classrooms

Abstract: This study explored the experiences of gateway course instructors during the implementation of pedagogical changes aimed at improving the success of diverse students. A detailed case study was built through analysis of peer observations, focus groups, oral and written reflections, student grades, in-depth interviews, and pre and post student surveys. Results showed that instructors faced three major challenges in implementing pedagogical changes: pragmatic challenges, student-centered challenges, and challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…One area that has received increasing attention since Hockings' review is the question of professional development opportunities connected to accessibility and inclusion (Considine et al, 2014;Heesink, de Koning, & Visser, 2015;Thomas & Heath, 2014). Recent scholarship suggests that development opportunities should be part of a systematic program of support (Moriña Díez, López Gavira, & Molina, 2015) and have measures in place to identify and avoid outcomes such as changes in attitude but not in practice (Lombardi, Murray, & Gerdes, 2011).…”
Section: Institutional Commitment and Managementmentioning
confidence: 99%
“…One area that has received increasing attention since Hockings' review is the question of professional development opportunities connected to accessibility and inclusion (Considine et al, 2014;Heesink, de Koning, & Visser, 2015;Thomas & Heath, 2014). Recent scholarship suggests that development opportunities should be part of a systematic program of support (Moriña Díez, López Gavira, & Molina, 2015) and have measures in place to identify and avoid outcomes such as changes in attitude but not in practice (Lombardi, Murray, & Gerdes, 2011).…”
Section: Institutional Commitment and Managementmentioning
confidence: 99%
“…While many SoTL scholars have explored questions about accessibility and inclusion in teaching and learning, much of this work tends to focus on particular pedagogical strategies deployed at the classroom level (e.g., Dierker, Alexander, Cooper, Selya, Rose, & Dasgupta, 2016;Smith, 2012) or on educational development initiatives that support such classroom-level work (e.g., Considine, Mihalick, Mogi-Hein, Penick-Parks, & Van Auken, 2014;Glowacki-Dudka, Murray, & Concepción, 2012). Such scholarship is undoubtedly significant and continues to make important contributions to the goals articulated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (Considine et al. ) found a variety of barriers to implementation of new pedagogies. Educators had limited time to select new texts, revise lesson plans, and work closely with at‐risk students, and they misjudged the amount of class time required for student‐centered learning activities.…”
Section: What Factors Interfere With the Adoption Of Inclusive Pedagogy?mentioning
confidence: 99%
“…Training is time consuming, and along with the work of changing course content and pedagogy, competes with other demands on instructors' time. A recent study (Considine et al 2014) found a variety of barriers to implementation of new pedagogies. Educators had limited time to select new texts, revise lesson plans, and work closely with at-risk students, and they misjudged the amount of class time required for student-centered learning activities.…”
Section: What Factors Interfere With the Adoption Of Inclusive Pedagogy?mentioning
confidence: 99%